2017
DOI: 10.1186/s40168-017-0380-5
|View full text |Cite
|
Sign up to set email alerts
|

Quinones are growth factors for the human gut microbiota

Abstract: BackgroundThe human gut microbiome has been linked to numerous components of health and disease. However, approximately 25% of the bacterial species in the gut remain uncultured, which limits our ability to properly understand, and exploit, the human microbiome. Previously, we found that growing environmental bacteria in situ in a diffusion chamber enables growth of uncultured species, suggesting the existence of growth factors in the natural environment not found in traditional cultivation media. One source o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
73
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(73 citation statements)
references
References 36 publications
0
73
0
Order By: Relevance
“…A few attempts have been made to discover microbial interactions via signaling molecules that promote the growth of specific microbial types. Short peptides (57), siderophores (58) and quinones (59) have been identified as growth-promoting factors for microbial types that cannot grow independently.…”
Section: Discussionmentioning
confidence: 99%
“…A few attempts have been made to discover microbial interactions via signaling molecules that promote the growth of specific microbial types. Short peptides (57), siderophores (58) and quinones (59) have been identified as growth-promoting factors for microbial types that cannot grow independently.…”
Section: Discussionmentioning
confidence: 99%
“…The PAB have been shown to affect the growth of a wide variety of microbes, including bacteria, yeasts and moulds. Most studies have focused on selectively inhibiting the growth of microbes (Holo et al, 2002;Lind et al, 2007;Schwenninger et al, 2008;Faye et al, 2011), but the PAB's properties of stimulating growth are also known (Kaneko, 1999;Jan et al, 2002;Warminska-Radyko et al, 2002); 1,4-dihydroxy-2-naphthoic acid secreted by PAB can stimulate the growth of Bifidobacteria and various other anaerobes (Kaneko, 1999;Fenn et al, 2017). In line with this, it was reported that P. acidipropionicii P169 could stimulate rumen feed degradation (Sanchez et al, 2014).…”
Section: Effects On Production Of Volatile Fatty Acids and Methanementioning
confidence: 93%
“…The PAB might stimulate the growth and activities of ruminal microorganisms by providing growth factors, e.g. 1,4-dihydroxy-2-naphthoic acid (Kaneko, 1999;Fenn et al, 2017).…”
Section: Feed Degradationmentioning
confidence: 99%
“…3, bottom panel). Similarly, Bilophila wadsworthia was previously recovered in mixed cultures, where growth depended on a "helper strain" producing essential growth-promoting factors (quinones) (39,42). Several bacteria can act as "helpers" supplying quinones, including E. lenta, Eubacterium rectale, and different Bacteroides species.…”
Section: Resultsmentioning
confidence: 99%